Changes of central macular thickness post intravitreal ranibizumab and its associated factors among diabetic macular oedema patients - Tahir, Nursyafiqah Md (2020)
Background: Intravitreal Ranibizumab (IVR) which is an anti-vascular endothelial growth factor (anti-VEGF) has become the preferred treatment option to improve the vision of diabetic macular oedema (DMO) patients. IVR acts by inhibits VEGF-A from binding to its receptors, leading to decreased in vascular permeability and thereby causing changes of Central Macular Thickness (CMT). The response to IVR treatment is considered optimal if the changes of CMT after three months is less or equal to 280 μm. Objectives: The objectives of this study were to estimate the mean of changes of CMT and the proportion of optimal treatment response after three injections of IVR and to identify associated factors of changes of the CMT among DMO patients. Methods: This was a cross-sectional study using secondary record review of the DMO patients who received three-month treatment of IVR in Hospital Universiti Sains Malaysia from 2016 to 2019. The CMT was measured by using Optical Coherence Tomography (OCT) machines. Changes of CMT was calculated based on the differences of thickness of central macula in μm between baseline and at month three. General linear regression was then applied to analyse the association of changes of CMT using STATA SE 14 software. Results: A total of 153 DMO patients were included. There were 69 (45.1%) male and 84 (54.9%) female patients with a mean (standard deviation (SD)) age of 57.5 (7.70) years and median (interquartile range (IQR)) of diabetes duration of 11 (9) years. The mean (SD) of changes of CMT was 155.5 (137.8) μm. After three injection of IVR, only 30.7% had optimal treatment response. Factors significantly associated with changes of CMT were baseline CMT (b =0.73; 95% CI: 0.63,0.84; p = <0.001) and presence of subretinal fluid (SRF) (b= 35.43;95% CI:3.70,67.16; p = 0.029). These factors explained 58.3% of the variation in changes of CMT. Conclusions: There was less changes of CMT and less patients achieved optimal treatment response after three months of IVR treatment. Patients who presented with SRF and high baseline CMT had greater changes of CMT after receiving three injections of IVR treatments.